2005
DOI: 10.4102/sajip.v31i1.185
|View full text |Cite
|
Sign up to set email alerts
|

The construct equivalence of the job diagnostic survey for diverse South African cultural groups

Abstract: The Job Diagnostic Survey (JDS) and the Job Characteristics Model (JCM) have been widely used in South African organisations. The purpose of this study was to determine whether the JDS is useful if it is applied to a particular population or to groups from highly dissimilar backgrounds. Cultural diversity research has revealed differences between the values, attitudes and leadership styles of people from different cultural groups. In this study, Hackman and Oldham’s JDS was applied to Black and White employees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
1
13
0
2
Order By: Relevance
“…Hence the findings of the current study support hypothesis 4. The findings are consistent with those of Pillay (2009) and Vorster et al (2005) who argued that nurses are restricted from working to their full potential and providing total commitment as a result of their constrained environment. Pillay (2009) further asserted that they should be availability of protective materials and functional equipment to safeguard nurses from unnecessary accidents, as well the implementation of structures and processes to help nurses improve their personal safety skills.…”
Section: Paysupporting
confidence: 82%
“…Hence the findings of the current study support hypothesis 4. The findings are consistent with those of Pillay (2009) and Vorster et al (2005) who argued that nurses are restricted from working to their full potential and providing total commitment as a result of their constrained environment. Pillay (2009) further asserted that they should be availability of protective materials and functional equipment to safeguard nurses from unnecessary accidents, as well the implementation of structures and processes to help nurses improve their personal safety skills.…”
Section: Paysupporting
confidence: 82%
“…Schaap and Basson (2003) found evidence that the constructs measured by the PIB/SpEEx Motivation Index, namely internal locus of control and external locus of control, were equivalent for Black, Asian and White entry-level job applicants. Vorster, Olckers, Buys and Schaap (2005) investigated the equivalence of the structural model of the Job Diagnostic Survey and reported that the model held for Black and White groups. Only 22% of the respondents completed the questionnaire in their mother tongue (English) and it should be noted that approximately 69% of the White group did not complete the questionnaire in their mother tongue because a large percentage were Afrikaans speaking.…”
Section: Personality Testing and The Opq32mentioning
confidence: 99%
“…The fair testing of people from highly dissimilar backgrounds therefore poses a challenge for those who apply tests. Cultural diversity research has revealed differences, particularly between the values, attitudes and leadership styles of people from different cultural groups (Vorster, Olckers, Buys & Schaap, 2003). Cross-cultural studies suggest that linguistic proficiency, attitudes, motivation, values and other culture-specific factors all play an important role in differences between test response patterns that occur between groups (Schaap, 2003).…”
Section: Introductionmentioning
confidence: 99%